Significance and Challenges of Electronic Information Resources Management in University Libraries : A Systematic Literature Review - Yahaya, Abdullahi; Bappah , Magaji Abubakar (MiddleBelt Journal of Library and Information Science, 2016)
This paper provides a review on the significance and challenges of electronic information resources management (EIRs) in university libraries. The objectives of the study therefore are to identify the types of (EIRs) available in university libraries, the significance of (EIRs)in university libraries as well as the challenges affecting the management of (EIRs)in university libraries especially in developing countries. The review examines the concept and types of (EIRs). It also examines the significance of (EIRs) in university libraries as well as the challenges associated with the management of such resources. The paper concludes by stressing that low level of (EIRs) management in university libraries especially in developing countries are as result of the following: instability of power supply and slow speed network as a result of low bandwidth which affects the internet connectivity, inadequate well trained personnel with adequate knowledge of (EIRs) management, inadequate technological equipment, poor funding, absent of policy guidelines and lack of user education.